USE OF TECHNOLOGY IN MODERN CLASSROOM TEACHING - Sarvinoz Rakhimova Tolibovna (Journal of new century innovations, 2022)
Abstract: The modern, technological era has seen significant advancements in every discipline. As our awareness of the world grows, new advancements are revealed. These inventions help us grow as a species. The sector of education is changing significantly as a result of the development of this modern technology and the internet. Smart boards and e-books are used in place of the traditional blackboard books. The way that students learn has also changed, and they now depend more on contemporary technologies. Using the technology at their disposal, the teachers adapt their methods and strategies to teach the EFL/ESL students English while incorporating new technology into the classrooms. Some EFL/ESL professors even urge their students to use their phones in class to simplify their study. This essay focuses on research done on cell phones being used in class. Additionally, the benefits of adopting mobile apps for students are covered.